Application of muscadine grape (Vitis rotundifolia Michx.) pomace extract to reduce carcinogenic acrylamide. (1st September 2015) - Xu, Changmou; Yagiz, Yavuz; Marshall, Sara; Li, Zheng; Simonne, Amarat; Lu, Jiang; Marshall, Maurice R.
Highlights: Muscadine grape pomace extract could effectively reduce acrylamide in vitro . Inhibition of acrylamide by different polyphenols varied greatly. Significant inhibition was observed for skin and seed polyphenol fractions. Strong antioxidant activity of polyphenols doesn't mean high acrylamide inhibition. Polyphenols were found to directly trap acrylamide at high temperatures. Abstract: Acrylamide is a byproduct of the Maillard reaction and is formed in a variety of heat-treated commercial starchy foods. It is known to be toxic and potentially carcinogenic to humans. Muscadine grape polyphenols and standard phenolic compounds were examined on the reduction of acrylamide in an equimolar asparagine/glucose chemical model, a potato chip model, and a simulated physiological system. Polyphenols were found to significantly reduce acrylamide in the chemical model, with reduced rates higher than 90% at 100 μg/ml. In the potato chip model, grape polyphenols reduced the acrylamide level by 60.3% as concentration was increased to 0.1%. However, polyphenols exhibited no acrylamide reduction in the simulated physiological system. Results also indicated no significant correlation between the antioxidant activities of polyphenols and their acrylamide inhibition. This study demonstrated muscadine grape extract can mitigate acrylamide formation in the Maillard reaction, which provides a new value-added application for winery pomace waste.